Qualidade de efluentes de tanques de girino de Rã-Touro - Borges, Fernanda de Freitas [UNESP]; de Stéfani, Marta Verardino [UNESP]; do Amaral, Luiz Augusto [UNESP] (My University, 2014)
The objective of this study was to determine the quality of the effluent from ponds populated with bullfrog tadpoles by evaluating the physical, chemical and microbiological parameters of the water. Samples were collected bi-weekly on the ponds located at the bullfrog culture sector in the Caunesp. The experimental design was completely randomized with two treatments (inlet and outlet water) and six repetitions (ponds). There was no difference (P>0.01) among treatments for conductivity, however, the values varied in different samples according to growth of tadpoles. The values of temperature, pH, dissolved oxygen and nitrate were higher (P<0.01) in the inlet, while total phosphorus, ammonia, Escherichia coli, chemical oxygen demand (COD), biochemical oxygen demand (BOD5) and turbidity had increased concentrations in the outlet water. The total phosphorus and BOD5 concentrations were higher than permitted by Brazilian environmental legislation. The management adopted to rear bullfrog tadpoles increased the nutrients in the water, with the highest concentrations of ammonia and total phosphorus deriving mainly from the uneaten feed and animal excretion, the latter being the main factor for water eutrophication.
Quality of the effluents of bullfrog tadpole ponds
Keywords: Frog culture; Phosphorus; Water quality